2013
DOI: 10.4161/hv.26919
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in immunotherapy for non-small-cell lung cancer

Abstract: However, although therapeutic cancer vaccines are generally thought to be safe, severe adverse events should be monitored carefully when using immune checkpoint inhibitors. Here, we discuss recent advances and future perspectives of immunotherapy for patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Previous studies have suggested that optimal activation of effector T cells required 2 signals: an antigen-specific signal generated by the interaction between the antigen and the TCR (MHC-Ag-TCR) and a second signal resulting from the interaction between costimulatory molecules (B7-CD27). 25,26 We showed in this study that EGFR mutations caused a weakening of the immunogenicity, which impaired the antigen specific signal and caused the T cells to become blind to the tumor cells. As we all know, the CheckMate 026 clinical trial comparing first-line nivolumab with standard chemotherapy in NSCLC patients with PD-L1 5% was failed.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have suggested that optimal activation of effector T cells required 2 signals: an antigen-specific signal generated by the interaction between the antigen and the TCR (MHC-Ag-TCR) and a second signal resulting from the interaction between costimulatory molecules (B7-CD27). 25,26 We showed in this study that EGFR mutations caused a weakening of the immunogenicity, which impaired the antigen specific signal and caused the T cells to become blind to the tumor cells. As we all know, the CheckMate 026 clinical trial comparing first-line nivolumab with standard chemotherapy in NSCLC patients with PD-L1 5% was failed.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, aberrant PD-L1 and PD-L2 expression by cancer cells has been reported in many human malignancies (17)(18)(19). A series of clinical trials concerning the systemic administration of therapeutic antibodies for blocking PD-1 or PD-L1 have shown a promising clinical effect in various tumors (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Novel immunotherapy strategy is pending on histological definition of targets in tumor, and those targets can change in time [ 36 , 37 ]. So it is essential to search, for example, PD-L1 positivity for confirming reactivity of lung cancer on nivolumab before initiating treatment [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%